Green Building by Superadobe Technology: Innovative sustainable building method using Superadobe technology (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Superadobe is a form of earth bag construction that was developed by Iranian architect ―Nader Khalili‖. The technology uses layered long fabric tubes or bags filled with adobe to form a compression structure. The resulting beehive shaped structures employs corbelled arches, corbelled domes, and vaults to create single and double-curved shells that are strong and aesthetically pleasing. It has received growing interest for the past few years in the natural building and sustainability movements. In the last century earth bag buildings have undergone extensive research and are slowly gaining worldwide recognition as an optimum solution to the global epidemic of housing shortages. The technique‘s current pioneer is Nader Khalili who originally developed the superadobe system in 1984 in response to a NASA call for housing designs for future human settlements on the Moon and Mars. His proposal was to use moon dust to fill the plastic Superadobe tubes in layer. The Super Adobe Method is now use in Canada, Mexico, Brazil, Chile, Iran, India, Siberia, Thailand, as well as in the U.S.